Unit cost analysis of medical services at different levels of health facilities of a township in Myanmar - Athi Win Shwe (2020)
© Faculty of Pharmacy, Mahidol University (Thailand) 2018. In Myanmar, township health system, is the backbone of primary health care and provide comprehensive health service especially at rural area. Therefore healthcare services provided from health facilities in township healthcare system need an acceptable level of quality and at least possible cost. However, there is no comprehensive study in healthcare facilities to calculate the operating costs and the unit costs of the medical services they provide. The present study intended to calculate unit cost of basic medical services in different levels of health facilities (township hospital, station hospital and rural health center) under township healthcare system from hospital perspective by using standard costing method. The study results included unit cost of 28 basic medical services including OPD visit cost [1.6 USD (TH), 1.99 USD (SH), 0.54 USD (RHC)]; IPD admission cost [9.48 USD (TH) and 6.11 USD (SH)]; IPD hotel stay cost [2.02 USD (TH) and 1.20 USD (SH)]; surgery cost [10.37 USD (TH) and 10.97 USD (SH)]; delivery cost [200.32 USD at RHC] and home delivery cost [22.01 USD at RHC level]. The present study can identify areas where improvements in efficiency might get significant cost savings and can compare in different level of health facilities within township level. It also give evidence that detailed costing of hospital in Myanmar is feasible and it can provide information on the actual cost of basic medical services in different level of township health system in Myanmar which can be used in monitoring efficiency, resource allocation, hospital planning and management decision.